2011
DOI: 10.3810/pgm.2011.09.2471
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Titration and Conversion in Patients Receiving Morphine Sulfate and Naltrexone Hydrochloride Extended Release Capsules

Abstract: The study provides information about anticipated rates of achieving stable opioid dose in patients who received MS-sNT for up to 1 year to manage chronic, moderate-to-severe pain. Both opioid-naïve and opioid-experienced patients achieved a stable dose of MS-sNT, generally in ≤ 2 steps. Opioid experience and previous opioid use may influence ability to achieve a stable dose and number of steps required. More studies are needed on the anticipated experience of opioid titration/conversion to help physicians and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…An analysis of the root causes for opioid‐related deaths in the United States was recently published [40]. For this analysis, a panel of experts in pain medicine and public policy were convened to review results from a search of PubMed and state and federal government sources to assess frequency, demographics, and risk factors for opioid‐related overdose deaths from the previous decade.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of the root causes for opioid‐related deaths in the United States was recently published [40]. For this analysis, a panel of experts in pain medicine and public policy were convened to review results from a search of PubMed and state and federal government sources to assess frequency, demographics, and risk factors for opioid‐related overdose deaths from the previous decade.…”
Section: Resultsmentioning
confidence: 99%
“…For this analysis, a panel of experts in pain medicine and public policy were convened to review results from a search of PubMed and state and federal government sources to assess frequency, demographics, and risk factors for opioid‐related overdose deaths from the previous decade. The panel of experts concluded that clinicians' overreliance on published equianalgesic conversion tables, particularly when converting to methadone from another opioid, was one important contributor to opioid‐related deaths caused by physician's error [40].…”
Section: Resultsmentioning
confidence: 99%
“…Although this process takes a lot more time, the literature leads us to conclude that is likely to be much safer than switching all at once. In a study designed to determine the number of titration dose adjustments (“steps”) associated with attaining a stable dose of morphine and sequestered naltrexone extended‐release capsules, 272 of 319 (85%) patients who achieved a stable dose did so in ≤2 titration steps and 305 (96%) did so in ≤4 steps [14]. Therefore, although opioids can be converted within 2 steps most of the time, some patients may require up to a month or longer when being rotated from one opioid to another.…”
Section: Resultsmentioning
confidence: 99%
“…Opioid conversion (often used interchangeably with “rotation” or “switching” 12 ) has been defined as a change in opioid drug or route of administration with the goal of improving outcomes. 13 The mechanisms by which opioid conversion is thought to promote changes in either pain control or side effects are hypothesized to be the incomplete cross- tolerance between opioids, reducing the opioid load (incomplete tolerance) and/or side effects, and individual variation in opioid pharmacodynamics and pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“… 20 Post hoc analysis of data from an open-label safety study has reported the safe rotation and conversion of MSN in both opioid-naïve and opioid-experienced patients with moderate-to-severe CNCP. 12 …”
Section: Introductionmentioning
confidence: 99%